Persepsi Ibu, Guru dan Tenaga Kesehatan Tentang Obesitas Pada Anak Taman Kanak-Kanak - I G.A. Sri Dhyanaputri, Th. Ninuk Sri Hartini, Susi Ari Kristina (Berita Kedokteran Masyarakat (BKM), 2011)
Perception of Mothers, Teachers and Health Practitioners about Obesity in Kindergarten ChildrenBackground: Obesity has become a global epidemic. Programs for preventing and treating obesity in children required good cooperation from many parties. Threat perception of obesity in children, also the benefit and barriers in efforts regarding prevention and treatment of obesity were important features in determining involvement of mothers, teachers, and health practitioners in preventing and treating obesity in children.Objective: To explore perception of mothers, teachers, and health practitioners regarding obesity in the effort of preventing and treating obesity in kindergarten students in Denpasar City, Bali Province.Methods: This study use qualitative methods and involved 24 subjects, consisting of 19 mothers of kindergarten students, 2 kindergarten teachers, and 3 health practitioners. Data collection was conducted by doing Focus Group Discusion (FGD) in mothers, and also in-depth interview for mothers, teachers, and health practitioners. Further observation for school environment, measurement of the children’s nutritional status, food frequency, food record and activity record were also carried out. To ensure the validity of data collected, triangulation,member checking, debriefing and rich data were done. Data analysis was performed by using thematic analysis.Results: Mothers, teachers, and health practitioners felt that all children were vulnerable to obesity. Negative perception of obesity from mothers and teachers caused the obesity to be considered as unserious problems. Mothers who knew the effect of obesity on health, had relatives with history of degenerative diseases, and had previous obnoxious experience with obesity; worried about obesity in children. The lack of information collected by mothers and the many obstacles found regarding ways to prevent and treat obesity in children, cause mothers not to be able to do the efforts of preventing and treating obesity in children.Conclusion: Perception to threat of obesity in children was affected by perception of mothers, teachers, and health practitioners on vulnerability of children and seriousness of obesity threat to children. Perception of having bigger obstacle as compared to advantages, make mothers failed in doing preventive and treating efforts for obesity in children.Keywords: obesity, kindergarten students, perception of obesity in children, Denpasa